Social and emotional well-being of schoolchildren, an example of Kazakhstan in PISA-2018 (Journal of Educational Sciences, 2022)
Social and emotional well-being among schoolchildren is the main one, which affects the psychological state and academic employment of students. During distance learning, schoolchildren, the problem of social-emotional gain has acquired a greater transmission. However, today we have little quantitative data on the socio-emotional well-being of students in Kazakhstani schools. There is no data on the psychological and pedagogical conditions of the educational process. This article aims to cover the concepts of socio-emotional well-being, school climate, quantitative data coverage with the PISA-2018 surveys. Based on the analysis of PISA-2018 secondary data, it was revealed that about one third of Kazakhstani schoolchildren are not excluded from bullying. According to the data, slightly more than 5% of Kazakhstani schoolchildren missed school or were late for classes. 76% of students easily make friends at school, 69% of students feel part of the school community. However, 79% of students consider themselves outsiders in school. 78% feel "out of place" at school and 80% said they feel lonely. According to the results of PISA-2018, Kazakhstani schoolchildren are satisfied with their lives above the average of the countries participating in the study. In the context of the village-city, rural schoolchildren are more satisfied with life than their peers from cities. 45% of students in Kazakh schools worry about what others might think if they make a mistake. 34% are afraid of failure because this may negatively affect their future. In general, the results of the study should be cross-checked with data from the field study, and the validity of the test instrument, its translation, and consideration of socio-cultural differences should also be examined.Keywords: social and emotional well-being, school students, learners, school climate, school environment.